HIV/aids patients’ reflections on antiretroviral therapy - Galvão, Marli Teresinha Gimeniz; Gouveia, Aline de Souza; Fiúza, Maria Luciana Teles; Costa, Ênia (Rev Rene, 2011)
The goal of this research is to present reflects on the themes HIV/AIDS patients discussed in a self-help group regarding antiretroviral therapy (ARVT). It Is a descriptive, retrospective and documentary study. The records of 71 groups which were analyzed were held between 2007 and 2009 at a specialized outpatient clinic in Fortaleza-Ceará-Brazil. Statements about antiretroviral therapy were categorized through inferences on similar contents, as follows: 1. Experiencing daily life full of drugs, 2. Representations of ARVT on the body; 3. Facing secondary illnesses due to the use of the drugs and 4. Experiencing daily life positively due to the use of specific drugs. In conclusion, despite advances in ARVT, many difficulties are part of patients’ daily reality. This evidences the importance of group strategies to favor better coping with the disease and medication treatment, particularly as a result of experience exchange. Hence, nursing should be attentive to the development of group activities which may offer a better quality of life to the patients.